Myocard Injury in COVID-19 Patients After Application Of Umbilical Cord Mesenchymal Stem Cell (UC-MSC) as Adjuvant Therapy in Persahabatan Hospital - Mega Juliana; Triya Damayanti; Yasmina Hanifah; Erlina Burhan (Indonesian Society of Respirology (ISR), 2023)
Background: Myocardial injury was a frequent cardiovascular manifestation of COVID-19 and associated with high mortality. Cell-based approaches, primarily using mesenchymal stem cell (MSC) has demonstrated safety and possible efficacy as adjuvant therapy in COVID-19 patients. This study aims to evaluate myocardial injury in patients with moderate-severe and critically ill COVID-19 after the application of umbilical cord mesenchymal stem cell (UC-MSC) as adjuvant therapy in Persahabatan hospital. Method: This is a retrospective and prospective cohort study. A total of 28 subjects were allocated to 13 subjects in the control and 15 subjects in the experimental group. Subjects were given the standard treatment and UC-MSC or placebo. Myocardial injury is defined by an increase of troponin I >26 pg/ml. The biomarkers of troponin I, NT-proBNP and CRP was examined periodically. Cardiac pump evaluated by EF and TAPSE from echocardiography examination before and after UC-MSC application. The evaluation of myocardial injury, biomarkers, cardiac pump and 15-day mortality were observed between the two groups. Results: The incidence of myocardial injury was 28,6% of total subjects. Subjects with worsening myocardial injury were higher in the control group (6 subjects) than the experimental group (4 subjects) although not statistically significant. The difference in biomarkers (troponin I, NT- pro-BNP and CRP), cardiac pump function (EF and TAPSE) and 15-day mortality between two groups were not statistically significant. There was a trend of decreasing troponin I, NT-proBNP and CRP in the experimental group. Conclusion: UC-MSC application can be an option as adjuvant therapy in improving myocardial injury of moderate-severe and critically ill COVID-19 patients.